Selection of the main components and study of their influence on the quality indicators of raw smoked sausages - M. A. Gasheva (Новые технологии)
To date, it is known that functional nutrition products account for 3% of all known food products. Based on forecasts, in the coming decades, their percentage ratio will increase to 30–50% of the entire grocery market. The range of functional meat products is poorly developed, which is explained by the peculiarities of their production technology [5]. One of the tasks of functional nutrition in the production of sausages and sausage products is to minimize the fat content, reduce the amount of sodium nitrite, phosphate and nitrates, and include probiotics, prebiotics and other functional ingredients in the formulation. Raw smoked sausages are in great demand among consumers and have a long shelf life of up to 6 months. But at the same time, they have a long and time-consuming technological process that proceeds according to the traditional technological scheme for up to 45 days. In order to reduce the maturation time of raw smoked sausages, various starter cultures are added to the minced meat, as well as carbohydrates that serve as an energy source for microorganisms [6; 9]. Due to the impact of starter cultures on the pathogenic microflora of the product, their number is significantly reduced, the shelf life of finished products is increased, and the organoleptic characteristics of raw smoked sausages are improved [8]. Carbohydrates play an important role in the fermentation process; they influence the acquisition of taste in the finished product and, depending on the amount introduced, change the consistency of the product. Also, for starter bacterial cultures, carbohydrates are energy, i.e. food for lactic acid bacteria. Dry demineralized whey is used in the production of sausage products to reduce residual sodium nitrite, improve organoleptic parameters and enrich with whey proteins, vitamins and minerals [7; 9]. By introducing dry demineralized whey into raw smoked sausage, it is possible not only to shorten the fermentation time, improve the taste and smell of raw smoked sausages, but also to enrich it with proteins and trace elements necessary for vital activity, while giving the finished product functionality [9]. In this scientific article, the selection of starter and probiotic starter cultures for the production of raw smoked sausages with specified functional properties is carried out. The amount of demineralized serum introduced and its effect on the quality indicators of the finished product were determined.